Electronics : a complete course - Cook, Nigel P. , 1961- (Pearson Prentice Hall, 2004)
Provides comprehensive coverage of the three electronics fundamental courses; DC/AC, Devices and Digital. This work is intended for DC/AC, devices, digital electronics courses in high schools, vocational-technical schools and community colleges. It makes the world of electronics easily accessible in one text